Descrição de vídeo com multimedia content description interface (MPEG-7) - Almeida, Pedro (2003)
This article presents one brief introduction to the MPEG-7 standard, Multimedia Content Description Interface, and one of the possible applications to describe videos of a digital library, in a way that it makes possible indexing and searching this information.